Inhibition of Myostatin Reduces Collagen Deposition in a Mouse Model of Oculopharyngeal Muscular Dystrophy (OPMD) With Established Disease - Harish, Pradeep; Forrest, Leysa; Herath, Shanti; Dickson, George; Malerba, Alberto; Popplewell, Linda (Frontiers in Physiology, 2020)
Oculopharyngeal muscular dystrophy (OPMD) is a late-onset muscle disease presented by ptosis, dysphagia and limb weakness. Affected muscles display increased fibrosis and atrophy, with characteristic inclusion bodies in the nucleus. Myostatin is a negative regulator of muscle mass, and inhibition of myostatin has been demonstrated to improve symptoms in models of muscular dystrophy. We systemically administered a monoclonal antibody to block myostatin in the A17 mouse model of OPMD at 52 weeks of age. The mice were administered a weekly dose of 10mg/kg RK35 intraperitonially for 10 weeks, following which histological analyses were performed on muscle samples. The administration of the antibody resulted in a significant decrease in serum myostatin and collagen deposition in muscles. However, minimal effects on body mass, muscle mass and myofibre diameter, or the density of intranuclear inclusions (a hallmark of disease progression of OPMD) were observed. This study demonstrates that inhibition of myostatin does not revert muscle atrophy in a mouse model with established OPMD disease, but is effective at reducing observed histological markers of fibrosis in the treated muscles.